Institutional reforms under 'New' Malaysia: the way forward - Jamaiudin, Norhaslinda (2019)
Remarkable history was created when Pakatan Harapan won and received a strong mandate to form the coalition government in 14th general election. This newly elected government thrives to create a ‘New Malaysia’ with new agenda in place. The creation of ‘New Malaysia’ is based on five pillars and substantial interest has been devoted for political and institutional reforms, the second pillar of new governing agenda. This is seen as strategic actions to fulfill hopes of all Malaysians and to rebuild this nation. Rebuilding nation requires transformation through political and institutional reforms. In the case of new Malaysia, institutional reforms can be contextualized into three main aspects namely fiscal, regulatory and administrative. Such attempt is critical as it serves as the foundation to uplift government’s competency, accountability and transparency (C.A.T). Presumably, institutional quality and government’s competency, accountability and transparency will be improved through extensive institutional reforms and beyond that reform is expected to bring fundamental change in governance and to restore public trust which has been at the deficit level in the past few years. How effective these reforms have been in elevating trust in the context of ‘New Malaysia’? Does reform enhance government’s competency, accountability and transparency (C.A.T)? Has it lived up to expectation and improve deficit trust among public and what are the challenges? Guided by social capital theory, this paper aims to examine different types of institutional reforms and to measure the mediation effects it have on public trust via three mediating variables namely government’s competency, accountability and transparency. Hierarchical regression analysis techniques will be used to measure the mediating effect between variables. A hierarchical regression analysis using public trust as the outcome variable will be employed using institutional reforms in the first step and C.A.T as predictors in the second step. This analysis allows the examination of whether institutional reforms predict public trust and whether this relation would be stronger/ weaker in the presence of C.A.T as mediator.